Fabrication and Electrochemical Behavior Investigation of a Pt-Loaded Reduced Graphene Oxide Composite (Pt@rGO) as a High-Performance Cathode for Dye-Sensitized Solar Cells - Viet Hai Le; Thai Hoang Nguyen; Huu Hieu Nguyen; Le Thanh Nguyen Huynh; An Le Vo; Thi Kim Tuyet Nguyen; Duc Thinh Nguyen; Vinh Quang Lam (International Journal of Photoenergy)
A platinum-reduced graphene oxide thin film composite (Pt@rGO, 100 nm) was prepared on a fluorine-doped tin oxide- (FTO-) coated glass substrate by a screen printing method using a Pt@rGO screen printing paste (0.12% Pt; Pt/rGO=1.5 w/w). The as-prepared electrode (denoted as Pt@rGO/FTO) was used as the cathode for the assembly of dye-sensitized solar cells (DSSCs). It showed a well-dispersed and high loading of Pt on rGO surface with a particle size distributed around 10 nm. The redox behavior of ferrocene was performed at Pt/FTO, Pt@rGO/FTO, and rGO/FTO electrodes by a cyclic voltammetry (CV) method. The kinetic parameters, in particular, the standard reduction potential (E0, V), the transfer coefficient (α), the heterogeneous rate constant (k0, cm·s-1), and the diffusion coefficient (D, cm2 s-1), were determined by CV data treatment using convolution-deconvolution and fitting methods. The values of E0, α, k0, and D at Pt@rGO/FTO electrode were, respectively, 326 mV, 0.471, 3.33 cm·s-1, and 4.19 cm2·s-1, equivalent to those of Pt/FTO electrode (340 mV, 0.474, 3.18 cm·s-1, and 4.19 cm2·s-1). The Pt@rGO/FTO electrode exhibited excellent electrocatalytic activity compared to that of Pt thin film (Pt/FTO electrode) prepared from Pt commercial paste. The heterogeneous electron transfer rate constant k0 (cm·s-1) for I3-/I- at Pt@rGO/FTO is 1.3 times faster than that at Pt/FTO. The energy conversion efficiency of the DSSCs assembled from Pt@rGO-DSSC cathode reached 7.0%, an increase of 20.7% over the commercial Pt-based cathode (Pt-DSSC, 5.8%). The rGO component in the Pt@rGO composite plays two important roles: (i) facilitating the electron transfer between Pt NPs catalyst and the FTO substrate via the bandgap effect and (ii) the enlargement catalytic surface area of Pt NPs via the loading effect. The rGO material has, therefore, potential to replace the Pt content and improve the performance of the DSSC device.